2021
DOI: 10.35229/jaes.993377
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus ile Enfekte Köpeklerde Nötrofil/Lenfosit, Monosit/Lenfosit ve Platelet/Lenfosit Oranlarının Belirlenmesi

Abstract: Öz: Nötrofil/lenfosit oranı (NEU/LYM), monosit/lenfosit oranı (MONO/LYM), ve platelet/lenfosit oranı (PLT/LYM) inflamasyonun ucuz, tekrar kullanılabilen biyobelirteçlerini oluşturmaktadır. Bu çalışma ilk defa parvovirus enfeksiyonu (PVE) şekillenmiş köpeklerde NEU/LYM, MONO/LYM ve PLT/LYM değerlerini ortaya koymaktadır. Çalışmanın amacını ise tedavi öncesi PVE ile pozitif köpeklerin NEU/LYM, MONO/LYM ve PLT/LYM değerlerinin, sağlıklı kontrollere göre karşılaştırılması oluşturmuştur. On sekiz sahipli, 2-6 aylık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
4
3
1
Order By: Relevance
“…We found 7.6 as the cutoff value for NEU/LYM for the CDV infected dogs for distinguish them from healthy ones, similarly Hodgson et al (2018). Contrary to other studies (Çakir & Pekmezci 2019;Benvenuti et al, 2020;Pekmezci & Çolak, 2021), our NEU/LYM ratio was found to be high in the control dogs.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…We found 7.6 as the cutoff value for NEU/LYM for the CDV infected dogs for distinguish them from healthy ones, similarly Hodgson et al (2018). Contrary to other studies (Çakir & Pekmezci 2019;Benvenuti et al, 2020;Pekmezci & Çolak, 2021), our NEU/LYM ratio was found to be high in the control dogs.…”
Section: Discussioncontrasting
confidence: 78%
“…Meanwhile we found the mean MONO/LYM ratios of the infected dogs with B. burgdorferi and control group 0.7 and 0.4, respectively. Although a similar situation was observed in another of previously study, the mean MONO/LYM ratio in the PVI and control group was found to be 1.2, and 0.4, respectively (Pekmezci & Çolak, 2021). Contrary to previously reports (Çakir & Pekmezci 2019;Pekmezci & Çolak, 2021) we found a median MONO/LYM level as 2.33 in the CDV infected dogs.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations